Old-age mental telehealth services at primary healthcare centers in low- resource areas in Greece: design, iterative development and single-site pilot study findings - Antonios Politis; Theofanis Vorvolakos; Evaggelia Kontogianni; Maria Alexaki; Eleni-Zacharoula (Eliza); Eleutheria Aggeletaki; Maria Gkampra; Maria Delatola; Antonis Delatolas; Apostolos Efkarpidis; Elissavet Thanopoulou; Konstantinos Kostoulas; et al. (BMC, 2023)
Abstract Background Even though communities in low-resource areas across the globe are aging, older adult mental and cognitive health services remain mainly embedded in tertiary- or secondary hospital settings, and thus not easily accessible by older adults living in such communities. Here, the iterative development of INTegRated InterveNtion of pSychogerIatric Care (INTRINSIC) services addressing the mental and cognitive healthcare needs of older adults residing in low-resource areas of Greece is depicted. Methods INTRINSIC was developed and piloted in three iterative phases: (i) INTRINSIC initial version conceptualization; (ii) A 5-year field testing in Andros island; and (iii) Extending the services. The INTRINSIC initial version relied on a digital platform enabling videoconferencing, a flexible battery of diagnostic tools, pharmacological treatment and psychosocial support and the active involvement of local communities in service shaping. Results Ιn 61% of the 119 participants of the pilot study, new diagnoses of mental and/or neurocognitive disorders were established. INTRINSIC resulted in a significant reduction in the distance travelled and time spent to visit mental and cognitive healthcare services. Participation was prematurely terminated due to dissatisfaction, lack of interest or insight in 13 cases (11%). Based on feedback and gained experiences, a new digital platform, facilitating e-training of healthcare professionals and public awareness raising, and a risk factor surveillance system were created, while INTRINSIC services were extended to incorporate a standardized sensory assessment and the modified problem adaptation therapy. Conclusion The INTRINSIC model may be a pragmatic strategy to improve access of older adults with mental and cognitive disorders living in low-resource areas to healthcare services.